2019
DOI: 10.3390/app9245293
|View full text |Cite
|
Sign up to set email alerts
|

Role of Melatonin to Enhance Phytoremediation Capacity

Abstract: Phytoremediation is a green technology that aims to take up pollutants from soil or water. Metals are one of the targets of these techniques due to their high toxicity in biological systems, including plants and animals. Their elimination or, at least, decrease will help keep them from being incorporated in the trophic chain and thus reaching animal and human food. The metal removal efficiency of plants is closely related to their growth rate, tolerance, and their adaptability to different environments. Melato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3
1

Relationship

4
6

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 124 publications
0
30
0
Order By: Relevance
“…Some representative examples of melatonin induction by drought can be consulted in studies on Arabidopsis [ 24 ], barley [ 49 ], bermudagrass [ 67 ], apple [ 53 ], grapevine [ 56 ], and rice [ 72 ]. In these cases, an increase in the melatonin level, between 2- and 6-fold, in one or more transcripts of melatonin biosynthesis enzymes due to stress conditions have been described [ 72 , 73 ].…”
Section: Melatonin-induced Drought Stress Tolerancementioning
confidence: 99%
“…Some representative examples of melatonin induction by drought can be consulted in studies on Arabidopsis [ 24 ], barley [ 49 ], bermudagrass [ 67 ], apple [ 53 ], grapevine [ 56 ], and rice [ 72 ]. In these cases, an increase in the melatonin level, between 2- and 6-fold, in one or more transcripts of melatonin biosynthesis enzymes due to stress conditions have been described [ 72 , 73 ].…”
Section: Melatonin-induced Drought Stress Tolerancementioning
confidence: 99%
“…The potential of melatonin to mobilize toxic metals through phytochelatins, their transport, and sequestration adds to the general bio-stimulatory effect of melatonin on plants, resulting in a high degree of plant tolerance against heavy metals. Furthermore, the improvement in the absorption and metabolism of elements such as nitrogen, phosphorous, and sulfur helps the process of phytoremediation [50]. Although data are still limited, it seems that the presence of several stressors (e.g., metals and drought) synergistically induces the response of melatonin biosynthesis, which reinforces the overall response of the system.…”
Section: Heavy Metal and Chemical Stressmentioning
confidence: 99%
“…The modulation of an antioxidant enzyme’s level and its activity in order to improve the detoxification of ROS (H 2 O 2 , O 2 − ) is considered to be fundamental to enhance stress tolerance of plants [ 26 , 27 ]. In addition, MT is capable of inducing gene expression under abiotic and biotic stresses, germination, growth, development activities etc., [ 10 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. With respect to the role of melatonin in heat tolerance, many studies reported that exogenous treatment with MT enhances tomato seedling tolerance to high temperatures by improving their antioxidant defense system [ 39 , 40 , 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%